Healthcare-associated infections: epidemiology, antimicrobial resistance, and infection control challenges: a systematic review - Hamidreza Nassehinia; Rosita Saeidi; Fariba Yaghoubi; Ali Haghbin; Ali Akbar Mohammadi (Reviews on Environmental Health, 2026)
Abstract Healthcare-associated infections (HAIs), also known as nosocomial infections, remain one of the most significant challenges facing healthcare systems worldwide. These infections affect hospitalized patients and may also pose a risk to healthcare workers and individuals exposed to healthcare environments. HAIs are associated with increased morbidity, mortality, prolonged hospitalization, and substantial healthcare costs. Although previous studies have investigated different aspects of HAIs, evidence remains fragmented, and few reviews have comprehensively integrated epidemiology, antimicrobial resistance, and infection prevention and control (IPC) challenges. To address this gap, this systematic review aimed to comprehensively synthesize the available evidence on the epidemiology of HAIs and the major challenges related to antimicrobial resistance, infection prevention, and infection control. This systematic review was conducted in accordance with the Preferred Reporting Items for PRISMA 2020 guidelines. A comprehensive literature search was performed, for studies published between 1980 and 2025. Search terms included HAIs, antimicrobial resistance, multidrug-resistant (MDR) pathogens, infection prevention, and infection control (IPC). Studies addressing at least two aspects of prevention, diagnosis, management, or infection-control challenges were considered eligible. After screening 190 records, 43 high-quality studies with a Newcastle–Ottawa Scale (NOS) score of ≥6 were included in the final review. All studies were independently assessed by two reviewers, and disagreements were resolved through consultation with a third reviewer. The reviewed evidence indicated that urinary tract infections, respiratory tract infections, bloodstream infections, and skin and soft tissue infections were among the most frequently reported HAIs. Intensive care units (ICUs) were identified as the highest-risk hospital settings for infection occurrence and transmission. Furthermore, the emergence and spread of MDR microorganisms have become a major obstacle to effective IPC. The findings consistently demonstrated that adherence to hand hygiene practices remains one of the most effective measures for reducing pathogen transmission and preventing HAIs. Nosocomial infections continue to represent a major threat to patient safety and healthcare quality. Improving awareness of HAIs, strengthening IPC programs, promoting compliance with evidence-based preventive measures, and enhancing healthcare workers’ adherence to infection-control practices can substantially reduce the burden of these infections. The findings of this review provide evidence to support healthcare professionals, hospital administrators, and policymakers in developing evidence-based strategies to strengthen IPC programs, optimize antimicrobial stewardship, and improve patient safety.